Unconfined Mechanical Properties of Nanoclay Cement Compound Modified Calcareous Sand of the South China Sea - Wei Wang; Jian Li; Jun Hu (Advances in Civil Engineering)
Calcareous sand is characterized by low strength, multiporosity, and high-pressure shrinkage. This often leads to poor engineering properties. Therefore, it is often necessary to reinforce the calcareous sand in order to meet the actual engineering demand for bearing capacity. To study the modification effect of calcareous sand of nanoclay by cement, mechanical tests and microscopic tests of the cement calcareous sand (CCS) modified by different nanoclay content and cement content were conducted. Through the unconfined compressive test, the mechanical properties of nanoclay and cement compound modified calcareous sand (NCCS) were studied. The micromechanism of nanoclay and cement composite modified calcareous sand was analyzed by SEM. Representative curves of data groups of stress and strain data were obtained by the fusion algorithm, which effectively circumvented the discrete distribution of determined data. Test results showed that the following: (1) The compressive property of CCS could be improved by the admixture of nanoclay, and the optimum admixture ratio was 8%. (2) The admixture of nanoclay could enhance the deformation modulus of CCS and improve the resistance of CCS against external load deformation capacity. (3) Nanoclay could increase the density of the internal structure of CCS and improve its mechanical properties.